Quercetin and derivatives: useful tools in inflammation and pain management. (January 2017) - Carullo, Gabriele; Cappello, Anna Rita; Frattaruolo, Luca; Badolato, Mariateresa; Armentano, Biagio; Aiello, Francesca
Inflammation represents a very frequent condition in humans; it is often underestimated, making the problem an increasingly alarming phenomenon. For these reasons, conventional therapies are losing their effectiveness, leaving room for innovative therapies. In this field, natural products showed their efficacy in various diseases; and flavonoids, in particular quercetin, is known for its broad range of activities. In this review, we have highlighted its efficacy in various models of inflammation, focusing also on the activity of its semisynthetic derivatives, and those naturally present in plant extracts. Finally, the analgesic property of quercetin, intrinsically linked to its anti-inflammatory action, has been also evaluated, to investigate about an innovative approach to this interesting natural compound, such as analgesic remedial.